Utility of Paraneoplastic Antibody Testing in the Diagnosis of Motor Neuron Disease. Issue 2 (December 2015) - Al-Bustani, Najwa; Simonson, William; Marshall, Desiree A.; Vetrovs, Jennifer; Wener, Mark H.; Weiss, Michael D.; Wang, Leo H.
Abstract: Objective: To evaluate the role of paraneoplastic autoantibody testing in the diagnosis of motor neuron disease (MND). Background: There have been rare case reports of paraneoplastic MND that have prompted many physicians to test for paraneoplastic autoantibodies in patients with MND. Our study is the first to determine the utility of such testing. Methods: Retrospective chart review of patients with MND from a tertiary referral center from 2007 to 2014. Results: Of 316 patients with MND reviewed, 44% (n = 138) were evaluated by a Mayo Clinic paraneoplastic autoantibody panel. Of note, 73% of these patients (n = 101) were diagnosed with amyotrophic lateral sclerosis, fulfilling possible, probable, or definite revised El Escorial criteria. Of note, 9% of patients (13/138) of those who had paraneoplastic antibody testing performed were positive for at least 1 paraneoplastic antibody. Three patients had negative testing for malignancy. None had a different disease course than expected. Conclusions: Testing for paraneoplastic antibodies does not seem to change the diagnosis, management, or outcome in the setting of MND and is therefore of limited value.